Back Cover Image, Volume 93, Number 7, July 2021. Issue 7 (25th May 2021) - Bramante, Carolyn T.; Buse, John; Tamaritz, Leonardo; Palacio, Ana; Cohen, Ken; Vojta, Deneen; Liebovitz, David; Mitchell, Nia; Nicklas, Jacinda; Lingvay, Ildiko; Clark, Jeanne M.; Aronne, Louis J.; et al.
Abstract : Back Cover Caption : The cover image is based on the Research Article Outpatient metformin use is associated with reduced severity of COVID‐19 disease in adults with overweight or obesity by Carolyn T. Bramante et al., https://doi.org/10.1002/jmv.26873 . Design Credit: Andy Grams.